Runx2/DICER/miRNA Pathway in Regulating Osteogenesis. Issue 1 (26th April 2016) - Zheng, Leilei; Tu, Qisheng; Meng, Shu; Zhang, Lan; Yu, Liming; Song, Jinlin; Hu, Yun; Sui, Lei; Zhang, Jin; Dard, Michel; Cheng, Jessica; Murray, Dana; et al.
Abstract : DICER is the central enzyme that cleaves precursor microRNAs (miRNAs) into 21–25 nucleotide duplex in cell lineage differentiation, identity, and survival. In the current study, we characterized the specific bone metabolism genes and corresponding miRNAs and found that DICER and Runt‐related transcription factor 2 (Runx2) expressions increased simultaneously during osteogenic differentiation. Luciferase assay showed that Runx2 significantly increased the expression levels of DICER luciferase promoter reporter. Our analysis also revealed weaker DICER expression in embryos of Runx2 knock out mice (Runx2 −/−) compared with that of Runx2 +/− and Runx2 +/+ mice. We further established the calvarial bone critical‐size defect (CSD) mouse model. The bone marrow stromal cells (BMSCs) transfected with siRNA targeting DICER were combined with silk scaffolds and transplanted into calvarial bone CSDs. Five weeks post‐surgery, micro‐CT analysis revealed impaired bone formation, and repairing in calvarial defects with the siRNA targeting DICER group. In conclusion, our results suggest that DICER is specifically regulated by osteogenic master gene Runx2 that binds to the DICER promoter. Consequently, DICER cleaves precursors of miR‐335‐5p and miR‐17‐92 cluster to form mature miRNAs, which target and decrease the Dickkopf‐related protein 1 (DKK1), and proapoptotic factor BIM levels, respectively, leading to an enhanced Wnt/β‐catenin signaling pathway. These intriguing results reveal a central mechanism underlying lineage‐specific regulation by a Runx2/DICER/miRNAs cascade during osteogenic differentiation and bone development. Our study, also suggests a potential application of modulating DICER expression for bone tissue repair and regeneration. J. Cell. Physiol. 232: 182–191, 2017. © 2016 Wiley Periodicals, Inc. Abstract : These intriguing results reveal a central mechanism underlying lineage‐specific regulation by a Runx2/DICER/miRNAs cascade during osteogenic differentiation and bone development. This cell‐ and development‐specific regulation is essential and mandatory for the initiation and progression of osteogenic differentiation. Furthermore, our study also suggests a potential application of specifically regulating DICER for bone tissue repair and regeneration.